New rank-based tests and estimators for common primitive shocks - Federico Carlini; Mirco Rubin; Pierluigi Vallarino (Tinbergen Institute, 2025)
We propose a new rank-based test for the number of common primitive shocks, q, in large panel data. After estimating a VAR(1) model on r static factors extracted by principal component analysis, we estimate the number of common primitive shocks by testing the rank of the VAR residuals' covariance matrix. The new test is based on the asymptotic distribution of the sum of the smallest r - q eigenvalues of the residuals' covariance matrix. We develop both plug-in and bootstrap versions of this eigenvalue-based test. The eigenvectors associated to the q largest eigenvalues allow us to construct an easy-to-implement estimator of the common primitive shocks. We illustrate our testing and estimation procedures with applications to panels of macroeconomic variables and individual stocks' volatilities.
Keywords: C12; C23; C38; 330; Common primitive shocks; Dynamic factor models; Rank tests; Distribution of eigenvalues; Principal component analysis